1966
DOI: 10.1039/c19660000772
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthesis of glauconic acid: C9 precursors

Abstract: This is a general reaction of y-bromo-a /3-unsaturated esters.The general reaction of a-keto-esters with the phosphonate anions derived from a-bromo-esters gives maleic, but not fumaric, esters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…This suggests that the maleidride BGC identified within the T. atroroseus IBT 11181 genome may encode the production of 2, and likely glaucanic acid 3, a predicted precursor to 2. 18,29 Pitt is not publicly available, 14 but T. stipitatus cluster 2 demonstrates complete synteny in terms of the encoded activities and order of the genes in the cluster, therefore we have named the genes within this cluster according to the P. dangeardii Pitt BGC (see Figure S37). The five other orphan maleidride BGCs identified through cblaster 24 cannot be linked to the production of any known maleidrides, so are likely to encode novel maleidrides.…”
Section: Newly Identified Maleidride Bgcsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the maleidride BGC identified within the T. atroroseus IBT 11181 genome may encode the production of 2, and likely glaucanic acid 3, a predicted precursor to 2. 18,29 Pitt is not publicly available, 14 but T. stipitatus cluster 2 demonstrates complete synteny in terms of the encoded activities and order of the genes in the cluster, therefore we have named the genes within this cluster according to the P. dangeardii Pitt BGC (see Figure S37). The five other orphan maleidride BGCs identified through cblaster 24 cannot be linked to the production of any known maleidrides, so are likely to encode novel maleidrides.…”
Section: Newly Identified Maleidride Bgcsmentioning
confidence: 99%
“…This family of enzymes are known to catalyse the reversible NAD(P)H-dependent reduction of a carbonyl-containing compound to the corresponding alcohol. 67 W. aquatica is known to produce a range of epiheveadrides (18)(19)(20)(21)(22)(23), including those where the carbonyls of the anhydrides are reduced. Therefore we speculate that EpiR14 is involved in catalysing this reduction.…”
Section: Aldo/keto Reductasementioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies [ 5 , 11 15 ] have begun to reveal the genetic basis and complexity of the biosynthetic pathways to these fascinating molecules. Isotopic labelling [ 16 18 ], heterologous expression experiments [ 11 , 13 , 15 ], gene knock-outs [ 5 , 12 , 14 ] and in vitro work [ 19 ] have led to the proposal that the biosynthetic pathway begins with precursors (e.g. 11 ) assembled by an iterative highly reducing polyketide synthase (hrPKS), where the chain length and level of saturation varies according to the structure of the mature natural product.…”
Section: Introductionmentioning
confidence: 99%
“…Barton and coworkers suggested that maleic anhydride 6 is the precursor of 1 . 6 Although indirect and direct evidence has accumulated for this hypothesis, 6 , 20 , 21 anhydride 6 has never been observed as a component of B. fulva fermentations. Subsequent feeding studies on the phomoidrides utilising synthetic precursor analogues by Sulikowski and coworkers 22 indicated that the monomeric nonadride precursor unit may be a carboxylated species, e.g.…”
mentioning
confidence: 99%